2015
DOI: 10.7567/jjap.54.100303
|View full text |Cite
|
Sign up to set email alerts
|

Dependence of memory characteristics of fullerene-containing polymer on the kind of gate metal

Abstract: The memory operation of [6,6]-phenyl-C 61 -butyric-acid-methyl-ester-containing polystyrene nanocomposites was investigated while varying the kind of gate metal used. Moderate magnitudes of flatband voltage shift were observed both after negative and positive programming voltages were applied to the Au gate. Excellent retention characteristics were obtained for electrons, whereas the retention time of holes was much shorter than that of electrons for the gate. An analysis of the band diagram indicated that car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…It had not been used as carrier conducting material of electronic devices and its characteristics related to carrier transport had not been investigated. On the other hand, a number of reports indicated that gate insulating organic polymers containing fullerene molecules, referred to as nanocomposite organic polymers, were promising for organic flash memories because of their relatively simple fabrication techniques [30][31][32][33][34][35]. In these nanocomposite organic polymers, the matrix polymers are not EB resist materials.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It had not been used as carrier conducting material of electronic devices and its characteristics related to carrier transport had not been investigated. On the other hand, a number of reports indicated that gate insulating organic polymers containing fullerene molecules, referred to as nanocomposite organic polymers, were promising for organic flash memories because of their relatively simple fabrication techniques [30][31][32][33][34][35]. In these nanocomposite organic polymers, the matrix polymers are not EB resist materials.…”
Section: Introductionmentioning
confidence: 99%
“…In these nanocomposite organic polymers, the matrix polymers are not EB resist materials. It has been suggested that electrons or holes are injected into and stored in the LUMO or HOMO levels of the fullerenes and the carriers are transferred through the levels in the nanocomposite organic polymers [32,33].…”
Section: Introductionmentioning
confidence: 99%
“…They have not been used as carrier conducting materials for electronic devices, and their characteristics related to carrier transport have not been investigated yet. On the other hand, there have been reports indicating that gate insulating organic polymers containing fullerene molecules, referred to as nanocomposite organic polymers hereafter, are promising materials for organic flash memories because of their relatively simple fabrication technique 26 31 . Since it is suggested that electrons or holes are injected into and stored in the LUMO or HOMO levels of the fullerenes and the carriers are transferred through the levels in the nanocomposite organic polymers, there is a possibility of creating EB-patternable electrically conductive nanocomposite organic polymers having submicron or nanometer lateral sizes if organic EB resists can be used for the matrix polymers.…”
Section: Introductionmentioning
confidence: 99%